2013
DOI: 10.1071/ah13051
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition prevalence in a medical assessment and planning unit and its association with hospital readmission

Abstract: Malnutrition is a significant problem in a MAPU setting, and patients screened at nutritional risk are at significantly higher risk of hospital readmission within 90 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…22 For example, Cederholm et al reported that mortality after hospitalization was significantly increased in patients with malnutrition compared with well-nourished patients. 23 Previous studies have also indicated that malnutrition was associated with hospital readmission 23,24 ; however, we failed to identify this association in our study population.…”
Section: Discussionmentioning
confidence: 59%
“…22 For example, Cederholm et al reported that mortality after hospitalization was significantly increased in patients with malnutrition compared with well-nourished patients. 23 Previous studies have also indicated that malnutrition was associated with hospital readmission 23,24 ; however, we failed to identify this association in our study population.…”
Section: Discussionmentioning
confidence: 59%
“…For example, exclusion of non‐English literature and studies describing services such as observation or short stay units that operate similarly to MAUs that did not comply with the IMSANZ standards. Some of these articles included topics relevant to the two main foci of this review (older people and MAUs) such as techniques in risk assessment, nursing models of care, diagnostic pathways for complex patients, cognitive screening for older people and the use of funnel plots to improve efficiency and reduce patient mortality .…”
Section: Discussionmentioning
confidence: 99%
“…Between 1999 and 2017, the MST was validated in acute, long-term, rehabilitation, and ambulatory care and oncology clinics in at least nine different countries. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] These studies revealed that the MST exhibited a moderate degree of validity, a moderate degree of agreement, and a moderate degree of inter-rater reliability in identifying malnutrition risk in adults ( Figure 2). The strength of evidence for the MST is Grade I, good/ strong with good generalizability.…”
Section: Positionmentioning
confidence: 99%